Students' Use of YouTube to Practice Speaking Skills - Elmi Khoirina; Netanya Pebrihani; Shaffa Novitasari (English Language Education Study Program of STKIP PGRI Banjarmasin, 2023)
ABSTRACT The objective of this research is that the researchers want to find out how students of the English Education Study Program at the University of Palangka Raya use YouTube as a learning medium to learn speaking practically and independently. This is because currently technology has developed rapidly. Many people take advantage of technology in educational life. Youtube is one of the media that has recently been widely used for various things, one of which is in the scope of education. This research is a descriptive qualitative research design that uses a survey as a case study. The subjects of this study are English Education students at University of Palangka Raya in academic year 2022/2023. There are six steps to conduct research using surveys. Those are planning and ensuring main questions, determining population, determining samples, contracting the research instrument, conducting the survey, and analyzing research data. The research data was analyzed qualitatively. The survey results stated that the majority of respondents said that they used Youtube to practice speaking skills such as grammar, pronunciation, vocabulary, facial expressions, intonation, and fluency. This researche can be concluded that the use of Youtube as a learning media in speaking class can help students to improve their speaking skills. Keywords: Students’ Use of Youtube, Youtube, Speaking Skills, Qualitative research, Survey, Case Study